111k views
4 votes
Urgent answer please
Ax+ay+xa+ya

1 Answer

3 votes

Answer:

Possible derivation:

d/dx(a x + a y(x) + x a + y(x) a)

Rewrite the expression: a x + a y(x) + x a + y(x) a = 2 a x + 2 a y(x):

= d/dx(2 a x + 2 a y(x))

Differentiate the sum term by term and factor out constants:

= 2 a (d/dx(x)) + 2 a (d/dx(y(x)))

The derivative of x is 1:

= 2 a (d/dx(y(x))) + 1 2 a

Using the chain rule, d/dx(y(x)) = (dy(u))/(du) (du)/(dx), where u = x and d/(du)(y(u)) = y'(u):

= 2 a + d/dx(x) y'(x) 2 a

The derivative of x is 1:

= 2 a + 1 2 a y'(x)

Simplify the expression:

= 2 a + 2 a y'(x)

Simplify the expression:

Answer: = 2 a

Explanation:

User Dave Mansfield
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.